Results of a comparative study of Nigella Sativa L. Seeds oils composition - S. V. Goryainov; A. V. Khromov; G. Bakureza; Esparsa Cesar; V. A. Ivlev; A. N. Vorobyev; R. A. Abramovich; O. G. Potanina; O. O. Novikov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
This article presents results of the chemical composition study of the seeds oils lipid complex of Nigella Sativa L. grown under various geographic conditions. The task of the comprehensive study of the chemical composition of the plant and its individual parts remains relevant due to the wide spectrum of its pharmacological activity.The aim of this work is a comparative study of the fatty acid composition, a non-saponifiable fraction and the composition of essential oils of Nigella Sativa L. seeds grown in different regions of the world.Materials and methods. The combination of chromatography-mass spectrometry and 1H-NMR spectroscopy methods made it possible to study the qualitative and quantitative composition of Nigella Sativa L. lipid complex seeds. All the experiments were carried out in accordance with the requirements of the State Pharmacopoeia, 14th Ed, given in the corresponding general pharmacopeial monographs.Results. Profiles have been established and the content of fatty acids, sterines, triterpene alcohols, essential oils and thymoquinone found out in the lipid complex, has been estimated. The saponifiable portion of the complex is represented by triglycerides (81.7-95.3%), di(3.9-15.2%) and monoglycerides (0.7-4.1%). They mainly contain linoleic (55.8-60.6%), oleic (21.8-24.6%), palmitic (10.0-12.8%), stearic (2.4-3.2 %) and cis-11.14-eicosadiene (2.3-2.6%) acids. In the lipid complex, the contents of sterines and triterpene alcohols were 0.4-0.7%; up to 70% of the fraction was represented by β-sitosterol (22.5-29.2%), cycloartenol (20.1-36.6%) and 24 methylenecycloartanol (9.5-19.9%). In the trace amounts (up to 1.0%), cholesterol has been detected in all the samples. In the lipid complexes, the content of thymoquinone ranged from 0.7 to 2.6%.Conclusion. A comparative study of the seeds lipid complex of Nigella Sativa L. grown under various geographic conditions, has been carried out. The marker compounds as well as their content standards for determining the authenticity of raw materials (thymoquinone, para-cimen, cis-11.14-eicosadienic acid), have been identified.